2020
DOI: 10.1002/er.6088
|View full text |Cite
|
Sign up to set email alerts
|

Online parameters identification and state of charge estimation for lithium‐ion batteries using improved adaptive dual unscented Kalman filter

Abstract: State of charge (SOC) is a vital parameter which helps make full use of battery capacity and improve battery safety control. In this paper, an improved adaptive dual unscented Kalman filter (ADUKF) algorithm is adopted to realize coestimation of the battery model parameters and SOC. Notably, the covariance matching method that can adapt the system noise covariance and the measurement noise covariance is used to improve the estimation accuracy. Besides, singular value decomposition (SVD) is utilized to deal wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Typical ECM models include the Rint model, 2 Thevenin model, PNGV model, 3 and the widely used resistance capacitance (RC) network models model. Lai et al 4 compared different RC models and found the first‐order RC (1RC) can simulate the dominant battery dynamics while keeping a low computing complexity. In contrast, the second‐order RC model improves the modeling accuracy at the expense of higher complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical ECM models include the Rint model, 2 Thevenin model, PNGV model, 3 and the widely used resistance capacitance (RC) network models model. Lai et al 4 compared different RC models and found the first‐order RC (1RC) can simulate the dominant battery dynamics while keeping a low computing complexity. In contrast, the second‐order RC model improves the modeling accuracy at the expense of higher complexity.…”
Section: Introductionmentioning
confidence: 99%
“…After that, different Bayesian state estimation algorithms are applied to estimate the battery SOC and capacity concurrently. The filters used include multi‐scale dual Kalman filters, 4,7 unscented Kalman filter (UKF), 8 the PI filter, 9 H infinity filters, 10 unscented particle filters (UPF), 11 and extended Kalman filter (EKF) 12…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the performance of this type of method is strongly depend on the quantity and quality of training data, and its estimation accuracy under different operating conditions still needs to be further verified 7 . Considering prediction performance and computation cost simultaneously, model‐based method seems more promising to be adopted in BMS to provide online SOC estimation 8‐11 . In this type of method, a sophisticated battery model is required to simulate battery dynamics primarily.…”
Section: Introductionmentioning
confidence: 99%
“…Among all commercially available lithium-ion batteries, the ternary lithiumion batteries are widely utilized because of their advantages of long service life, high energy density, superior performance at high and low temperatures, and environmental protection [5]. However, under certain operating conditions, the difference among all individual cells may result in battery over-charge and over-discharge, even explosions [6]. Therefore, the Battery Management System (BMS) plays a crucial role in assuring safety and monitoring the operating process [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the above-mentioned non-model-based methods, the model-based methods are more promising for EV application. The process of these approaches can be divided into three procedures: model building, identification of model parameters, and SOC estimation [6]. Many battery models have been reported to date, e.g., the electrochemical model [16], equivalent circuit models (ECMs) [17,18], and neural network models [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%